(untitled) (The Pakistan Development Review, 1989)
In recent years there has been much conceptual and empirical debate about the status of the informal sector and its role in the development of Third World countries. It was used by the International Labour Organization (ILO) as a policy tool for employment promotion, alleviation of poverty and elimination of income inequalities in developing countries [ILO (1972) and Weeks (1975)]. However, there is no dearth of studies which critically examine the informal sector [Bromley (1978); Tokman (1978); Gerry (1978) and Hosier (1987)]. Such studies have generated a fair amount of debate in the literature about the status of the informal sector [Richardson (1984); Moser (1984); House (1985) and Mehta (1985)].1 Based on a recent survey of some selected sub-groups of urban informal activities, this paper is an attempt to examine the status of the urban informal sector in Pakistan. Specifically, it will highlight some of our findings on the characteristics of its participants. The informal sector is defined in this study as representing establishments employing 10 workers or less. The plan of the paper is as follows. Section II gives a description of the survey data and its limitations. Section 1lI presents an empirical investigation of the characteristics and behaviour of the partiCipants. The last Section gives the conclusions of the study.